Clonal Analysis of the T-Cell Response to In Vivo Expressed Mycobacterium tuberculosis Protein Rv2034, Using a CD154 Expression Based T-Cell Cloning Method - Commandeur, Susanna (Public Library of Science, 2014)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a leading cause of death worldwide. A better understanding of the role of CD4(+) and CD8(+) T cells, which are both important to TB protection, is essential to unravel the mechanisms of protection and to identify the key antigens seen by these T cells. We have recently identified a set of in vivo expressed Mtb genes (IVE-TB) which is expressed during in vivo pulmonary infection in mice, and shown that their encoded antigens are potently recognized by polyclonal T cells from tuberculin skin test-positive, in vitro ESAT-6/CFP10-responsive individuals. Here we have cloned T cells specific for one of these newly identified in vivo expressed Mtb (IVE-TB) antigens, Rv2034. T cells were enriched based on the expression of CD154 (CD40L), which represents a new method for selecting antigen-specific (low frequency) T cells independent of their specific function. An Rv2034-specific CD4(+) T-cell clone expressed the Th1 markers T-bet, IFN-γ, TNF-α, IL-2 and the cytotoxicity related markers granzyme B and CD107a as measured by flow cytometry. The clone specifically recognized Rv2034 protein, Rv2034 peptide p81–100 and Mtb lysate. Remarkably, while the recognition of the dominant p81–100 epitope was HLA-DR restricted, the T-cell clone also recognized a neighboring epitope (p88–107) in an HLA-DR- as well as HLA-DQ1-restricted fashion. Importantly, the T-cell clone was able to inhibit Mtb outgrowth from infected monocytes significantly. The characterization of the polyfunctional and Mtb inhibitory T-cell response to IVE-TB Rv2034 at the clonal level provides detailed further insights into the potential of IVE-TB antigens as new vaccine candidate antigens in TB. Our new approach allowed the identification of T-cell subsets that likely play a significant role in controlling Mtb infection, and can be applied to the analysis of T-cell responses in patient populations.